TANGGUNG JAWAB SELLER JEJAKTAPAK PADA PERJANJIAN JUAL BELI ONLINE DALAM MEMENUHI HAK-HAK KONSUMEN - Arni Novi Sihombing; Firdaus Firdaus; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Internet-based sale and purchase transactions have reformed the sale and purchase transactions that occur conventionally, where transactions between business actors and consumers that were originally carried out directly become indirect transactions. One of the growing online buying and selling transaction sites in Indonesia is Shopee. The Government and Shopee site administrators have guaranteed consumer rights through the law, but there are still many cases of consumers who are disadvantaged in these online transactions.The issues discussed are first, regarding how the Implementation of Business Actors' Responsibilities in the online sale and purchase agreement in protecting consumer rights, and secondly the Efforts to Protect Consumer Rights in the Online Purchase Agreement.This thesis research method uses the type of sociological legal research. Sociological law research is research that wants to see the correlation between law and society, so that it can reveal the effectiveness of law enforcement in society. This research is descriptive. The data used are primary and secondary data, namely directly through respondents (field), Law Number 8 of 1999 Concerning Consumer Protection, legal journals and books relating to research. This data analysis is done qualitatively and deductive conclusions are drawn.From the results of research conducted by the author, found that many consumers are harmed as a result of not being able to return goods or funds to goods that do not match received. So there needs to be a change in the service of JejakTapak Seller to improve its services significantly so that consumers are satisfied with the service. Consumers also need to be more careful in shopping online.Keywords: Responsibility - Online Shopping